Supply Chain Strategy for World Price of Crude Palm Oil and Its Production on Palm Oil Marketing Margins in Indonesia: An Application of Pairwise Granger Causality - Syahril Syahril; Jumadil Saputra; Alisman Alisman; Affandi Affandi; Helmi Noviar; Rollis Juliansyah; Mahrizal Mahrizal (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to examine the supply chain strategy in causal relationship between world CPO price causality, production and marketing margin price using the Granger causality approach in the period January 2006-December 2017. This research proves that: (i) The results of the bivariate causality test explain that Indonesian CPO production has a single causality direction with world CPO prices. (ii) The results of the impulse response function and variance decomposition explain that the shock of the marketing margin variable gives a fluctuating response to fluctuations in world CPO prices, but the response is always positively given by the shock marketing margin in response to changes experienced by the variable world CPO prices. The results of this study are efforts to increase the price of CPO in the country by encouraging the development of palm oil derivative industries in increasing derivatives of high economic value products.